An Analysis of Teachers' Strategies on Students' Reading Comprehension in Online Learning at Junior High School - Rayhan Khairunnisa Situmorang; Fahriany Fahriany; Desi Nahartini (STABN RADEN WIJAYA WONOGIRI, 2022)
This research discussed reading skills, especially students' reading comprehension in online learning. Reading is an important activity in the learning process. However, most students only read the text, which made them not understand the content of the text, so students’ reading comprehension was not appropriately achieved. There is a close interaction between the reader and the text. Readers not only read but also have to understand the content of the reading. Students need to focus when reading a text, but with the current situation (COVID-19 pandemic), which has changed the learning process into online learning where the process has the distraction that can occur during the learning process, so it is important to know the strategies used by English teachers on students’ reading comprehension. Regarding this matter, this research was conducted on teachers’ strategies for students’ reading comprehension, especially in the eighth-grade students in Junior High School, using the qualitative method with the descriptive design. The researcher used observation, interview, and questionnaire as the instruments of the research. This research aims to describe and obtain the analysis data of the teachers’ strategies for students’ reading comprehension in online learning, the problems teachers face in maintaining students’ reading comprehension, and students’ responses to teachers’ strategies during online learning. The researcher concludes that teachers use “finding difficult vocabulary”, previewing strategy, reviewing strategy, discussion strategy, and resuming strategy so that students’ understanding of a text can be achieved during online learning. The problems teachers face are that students have limited vocabulary and lack the willingness to learn English. During the online learning process, students understand the subject matter about the text explained by the teacher, and they also show a positive response to teachers’ strategies.